Optically controlled grasping-slipping robot moving on tubular surfaces. Issue 2 (1st June 2022) - Guo, Hongshuang; Zeng, Hao; Priimagi, Arri
Abstract: Stimuli-responsive polymers provide unmatched opportunities for remotely controlled soft robots navigating in complex environments. Many of the responsive-material-based soft robots can walk on open surfaces, with movement directionality dictated by the friction anisotropy at the robot-substrate interface. Translocation in one-dimensional space such as on a tubular surface is much more challenging due to the lack of efficient friction control strategies. Such strategies could in long term provide novel application prospects in, e.g. overhaul at high altitudes and robotic operation within confined environments. In this work, we realize a liquid-crystal-elastomer-based soft robot that can move on a tubular surface through optical control over the grasping force exerted on the surface. Photoactuation allows for remotely switched gripping and friction control which, together with cyclic body deformation, enables light-fueled climbing on tubular surfaces of glass, wood, metal, and plastic with various cross-sections. We demonstrate vertical climbing, moving obstacles along the path, and load-carrying ability (at least 3 × body weight). We believe our design offer new prospects for wirelessly driven soft micro-robotics in confined spacing.